Cannabis Improves Obsessive-Compulsive Disorder—Case Report and Review of the Literature - Szejko, Natalia; Fremer, Carolin; Müller-Vahl, Kirsten R. (Frontiers in Psychiatry, 2020)
Although several lines of evidence support the hypothesis of a dysregulation of serotoninergic neurotransmission in the pathophysiology of obsessive-compulsive disorder (OCD), there is also evidence for an involvement of other pathways such as the GABAergic, glutamatergic and dopaminergic systems. Only recently, data obtained from a small number of animal studies alternatively suggested an involvement of the endocannabinoid system in the pathophysiology of OCD reporting beneficial effects in OCD-like behavior after use of substances that stimulate the endocannabinoid system. In humans, until today, only two case reports are available reporting successful treatment with dronabinol (tetrahydrocannabinol, THC), an agonist at central cannabinoid CB1 receptors, in patients with otherwise treatment refractory OCD as well as data obtained from a small open uncontrolled trial using the THC analogue nabilone: the combination of nabilone plus exposure-based psychotherapy was more effective than each treatment alone. These reports are in line with data obtained from a limited number of case studies and small controlled trials in patients with Tourette syndrome (TS), a chronic motor and vocal tic disorder often associated with comorbid obsessive compulsive behavior (OCB), reporting not only an improvement of tics, but also of comorbid OCB after use of different kinds of cannabis-based medicines including THC, cannabis extracts and flowers. Here we present the case of a 22-year-old male patient, who suffered from severe OCD since childhood, who significantly improved after treatment with medicinal cannabis with markedly reduced OCD and depression resulting in a considerable improvement of quality of life. In addition, we give a review of current literature on the effects of cannabinoids in animal models and patients with OCD and suggest a cannabinoid hypothesis of OCD.